A metabolic gene cluster in Lotus japonicus discloses novel enzyme functions and products in triterpene biosynthesis. Issue 3 (26th July 2013) - Krokida, Afrodite; Delis, Costas; Geisler, Katrin; Garagounis, Constantine; Tsikou, Daniela; Peña‐Rodríguez, Luis M.; Katsarou, Dimitra; Field, Ben; Osbourn, Anne E.; Papadopoulou, Kalliope K.
Summary: Genes for triterpene biosynthetic pathways exist as metabolic gene clusters in oat and Arabidopsis thaliana plants. We characterized the presence of an analogous gene cluster in the model legume Lotus japonicus . In the genomic regions flanking the oxidosqualene cyclase AMY2 gene, genes for two different classes of cytochrome P450 and a gene predicted to encode a reductase were identified. Functional characterization of the cluster genes was pursued by heterologous expression in Nicotiana benthamiana . The gene expression pattern was studied under different developmental and environmental conditions. The physiological role of the gene cluster in nodulation and plant development was studied in knockdown experiments. A novel triterpene structure, dihydrolupeol, was produced by AMY2. A new plant cytochrome P450, CYP71D353, which catalyses the formation of 20‐hydroxybetulinic acid in a sequential three‐step oxidation of 20‐hydroxylupeol was characterized. The genes within the cluster are highly co‐expressed during root and nodule development, in hormone‐treated plants and under various environmental stresses. A transcriptional gene silencing mechanism that appears to be involved in the regulation of the cluster genes was also revealed. A tightly co‐regulated cluster of functionally related genes is involved in legume triterpene biosynthesis, with a possible role in plant development. Abstract : See also the Commentary by Weng